تأثير الرش الورقي ببعض العناصر الصغرى ((B,Zn,Fe في الصفات الفيزيائية والكيميائية لثمار الليمون الحامض صنف الماير - مخول جرجس; بوعيسى عبد العزيز; محمد نسرين (Latakia University Journal -Biological Sciences Series, 2018)
نفذت التجربة خلال موسمي ( 2015 و2016) على أشجار الليمون الحامض صنف "الماير" بهدف دراسة تأثير التغذية الورقية بعناصر (البورون والزنك والحديد) في الصفات الفيزيائية والكيميائية للثمار ورشت هذه العناصر بشكل منفرد (كل عنصر لوحده) أو على شكل خليط . تم حساب متوسط كلاً من (طول ، قطر ، صلابة ، وزن وحجم الثمرة ) علاوة على ذلك حجم العصير وسماكة قشرة الثمرة، كما درست الصفات الكيمائية لعصير الثمار (المواد الصلبة الذائبة الكلية، السكريات الكلية، الحموضة الكلية ، فيتامين (Cولوحظ زيادة في جميع المؤشرات المدروسة في المعاملات المرشوشة مقارنة بالشاهد من قيم بالمادة مل عصير (%6.37-%3.33-%0.37-34.57مغ %)إلى قيم (-%9.33 %4.88- 1.89%- 43.5مغ %) في الموسم الأول وإلى قيم (-%9.75 %5.87- 3.32%- 45 مغ %) في الموسم الثاني على الترتيب ، وبنتيجة التحليل الإحصائي تبين وجود فروق معنوية بين جميع المعاملات المدروسة ومعاملة الشاهد مع تفوق معاملة الرش بخليط من البورون والزنك والحديد معاً في معظم المؤشرات المدروسة في الموسمين على باقي المعاملات، أما بالنسبة لسماكة قشرة الثمرة فلم يظهر التحليل الإحصائي أية فروق معنوية بين المعاملات. The experiment was conducted during the two seasons (2015 , 2016 ) on the Lemon trees cv (Meyer ) aiming at studying the effect of the foliar spraying with the nutrients ( boron , zinc and iron ) on physical and chemical properties of the fruits These nutrients were sprayed separately or as a mixture . The average of each of the physical properties of the fruit (length , width , firmness, volume and weight of the fruit ) , in addition to rind thickness and the fruits ` juice volume, ,the chemical properties of the fruit juice (total soluble solids, total sugars, total acidity, vitamin C) were studied. An increase was observed in all the studied parameters in the sprayed treatments compared to the control from( 6.37%- 3.33% -0.37% -34.57mg%)to(9.33% -4.88% -1.89% -43.5%) in the first season and( 9.75% 5.87- 3.32% - 45%) in the second season, respectively. As a result of the statistical analysis, there were significant differences between all the studied treatments and the control with overpass of the treatment of the three elements (iron chelate + boron oxide + zinc chelate ) of all treatments in the most of the studied figures in both seasons. Statistical analysis of the fruit rind thickness showed the absence of the significant differences among the studied treatments.